2021
DOI: 10.1101/2021.04.29.21256246
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is WHO International Standard for Anti-SARS-CoV-2 Immunoglobulin Clinically Useful?

Abstract: BackgroundThe introduction of vaccination against SARS-CoV-2 infection needs precise instruments for quality control of vaccination procedure, detection of poor immunological response and estimation of the achieved protection against the disease but also against infection and being infective.ObjectiveTo compare new automated SARS-CoV 2 Ig assay performance characteristics from the automated Elecsys SARS-CoV-2 S (Roche) with the new LIAISON® SARS-CoV-2 TrimericS IgG (DiaSorin) assay and their compatibility with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Such studies are not always able to establish reliable cutoffs, which could be applied to clarify which SARS-Cov-2 Abs levels would support re-vaccination of former infected or vaccinated people, owing to waning immunity. A surprising issue is that even though the sensitivity and specificity of various tests are excellent ( 72 ), the conversion of units from AU/ml to BAU/mL is not at all linear, as reported by others ( 12 , 73 , 74 , 75 ). Kim et al nicely illustrated that a factor 4.5 should be applied to convert Roche Elecsys anti-S Abs titers to Abbott IgG II ( 75 ).…”
Section: Introductionmentioning
confidence: 83%
“…Such studies are not always able to establish reliable cutoffs, which could be applied to clarify which SARS-Cov-2 Abs levels would support re-vaccination of former infected or vaccinated people, owing to waning immunity. A surprising issue is that even though the sensitivity and specificity of various tests are excellent ( 72 ), the conversion of units from AU/ml to BAU/mL is not at all linear, as reported by others ( 12 , 73 , 74 , 75 ). Kim et al nicely illustrated that a factor 4.5 should be applied to convert Roche Elecsys anti-S Abs titers to Abbott IgG II ( 75 ).…”
Section: Introductionmentioning
confidence: 83%
“…WHO international standard units are BAU ml −1 for anti-spike IgG to allow comparison across studies and platforms (20). The conversion factor for U ml −1 to BAU ml −1 for the Roche Elecsys® Anti-SARS-CoV-2 assay: (19) In addition, we selected 250 serum samples at random for assessment on a live virus neutralisation assay. Serum samples were heat-inactivated and a 2-fold dilution series was performed in 96-well plates.…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…The threshold value for antibody positivity for the Roche assay is 0.8 U ml -1 based on manufacturer instructions (18). The lower limit of quantification is 0.4 U ml -1 (19). Measurements below this value were truncated at 0.4 U ml -1 .…”
Section: Methodsmentioning
confidence: 99%
“…1) Antibody titers after the second dose 2) Factors affecting anti-spike protein antibody titers, and contributing to anti-spike protein antibody titers > 137 U/mL at 90 days after the second dose (Chloe's report indicated that the protection was 89.3% with antibody titers > 141BAU and 12.4% with antibody titers of 13 to 141BAU [16]. This antibody titer of 141 BAU corresponding to 89.3% protection was converted to 141*0.972BAU≒137 U/mL using the conversion formula based on the report by Krzysztof et al [17], which was assumed as a measure related to breakthrough infection. An analysis was performed based on whether this level was exceeded.…”
Section: Endpointsmentioning
confidence: 99%
“…In contrast, higher antibody titers than necessary are not required if antibody titers associated with breakthrough infection are maintained. Thus, the value corresponding to 89.3% protection as reported by Chloe [16] was converted to the antibody titer in this study [17], and an antibody titer of 137U/mL (assumed breakthrough level) was assumed as a measure related to breakthrough infection. Factors associated with antibody titers exceeding this level at 90 days were analyzed.…”
Section: Factors In Maintaining Antibody Titers That Are Not Expected...mentioning
confidence: 99%